Gendered Language in Everyday Conversation: A Sociolinguistic Perspective - Usman, Diandra; Mahajia, Lisnawati; Harmain, Aqif (Lembaga Publikasi Ilmiah Dwipantara, 2025)
Language is a powerful tool that not only facilitates communication but also reflects and reinforces social structures, including gender roles. While numerous studies have investigated gendered language, there remains a gap in understanding how everyday language subtly maintains gender hierarchies. This study aims to examine the use of gendered language in daily interactions from a sociolinguistic perspective. Utilizing a library research method, the study analyzes data from academic journals, textbooks, and reports using qualitative analysis to identify key themes in gendered language use. The findings reveal five major themes: gender differences in communication styles, power inequality in verbal interaction, language use reflecting stereotypes, awareness of inclusive language, and critiques of the binary approach. These findings highlight the dynamic role of language in shaping and maintaining gender ideologies. Ultimately, this research emphasizes the importance of inclusive and non-binary language practices in promoting gender equality across social contexts.